The imbuement of cultural elements in television advertisements: an Islamic perspective - Mokhtar, Aida (2019)
There has been wide coverage on Islamic ethics and Western ethics in the literature. It appears that more needs to be done in terms of examining culture from the Islamic perspective. The question arises as to how to determine which elements of culture ought to be adopted and which do not? There appears to be confusion on this matter as culture is created, learned and passed down from one generation to the next. Cultural elements are included in advertising messages and in the pragmatic ways of doing business. The paper defines culture, the role of culture in Islam and how to distinguish between acceptable and unacceptable cultural elements from the Islamic perspective.